2018
DOI: 10.1109/tvcg.2017.2658570
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality versus Virtual Reality for 3D Object Manipulation

Abstract: Virtual Reality (VR) Head-Mounted Displays (HMDs) are on the verge of becoming commodity hardware available to the average user and feasible to use as a tool for 3D work. Some HMDs include front-facing cameras, enabling Augmented Reality (AR) functionality. Apart from avoiding collisions with the environment, interaction with virtual objects may also be affected by seeing the real environment. However, whether these effects are positive or negative has not yet been studied extensively. For most tasks it is unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 16 publications
(18 reference statements)
1
37
4
1
Order By: Relevance
“…The results are partially in opposite with previous works that have compared VR and AR and could depend on the task to perform and on display fidelity, the accuracy and complexity of the technological systems (Arino et al, 2014;Botden et al, 2007;Boud et al, 1999;Cidota et al, 2016;Jones et al, 2008;Juan & Pérez, 2010;Khademi et al, 2013;Krichenbauer et al, 2017;Irawati et al, 2008;Lee et al, 2013;Möller et al, 2014). Indeed, the main previous comparison studies implemented non-complex tasks in which one task was proposed at a time, such as object manipulation, and our study included activity of daily life characterized by a succession of actions and/or two tasks at a time in a rich similar real environment.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The results are partially in opposite with previous works that have compared VR and AR and could depend on the task to perform and on display fidelity, the accuracy and complexity of the technological systems (Arino et al, 2014;Botden et al, 2007;Boud et al, 1999;Cidota et al, 2016;Jones et al, 2008;Juan & Pérez, 2010;Khademi et al, 2013;Krichenbauer et al, 2017;Irawati et al, 2008;Lee et al, 2013;Möller et al, 2014). Indeed, the main previous comparison studies implemented non-complex tasks in which one task was proposed at a time, such as object manipulation, and our study included activity of daily life characterized by a succession of actions and/or two tasks at a time in a rich similar real environment.…”
Section: Discussioncontrasting
confidence: 91%
“…Regarding the main aim, the results showed that the total times and the level times are lower in VR than AR. These results are partially on opposite with previous research and could depend on the differences in system used and the interaction tools, as well as on the complexity of the task (Arino et al, 2014;Botden et al, 2007;Boud et al, 1999;Cidota et al, 2016;Jones et al, 2008;Juan & Pérez, 2010;Khademi et al, 2013;Krichenbauer et al, 2017;Irawati et al, 2008;Lee et al, 2013;Möller et al, 2014). Indeed, previous studied have compared the two systems using a simple task, such as object manipulation or a pick and place task (Khademi et al, 2013), while our task based on a dailylife activity, characterized by a succession of actions and with more than one action at the same time.…”
contrasting
confidence: 65%
“…For instance, it was reported that users were able to complete tasks related to 3D object manipulation up to 22.5% faster in an AR environment than with VR. 19 The Microsoft HoloLens is a novel AR tool with potential for clinical and educational applications in health care. Medical education is transforming by using safer simulation technologies.…”
Section: Discussionmentioning
confidence: 99%
“…We force upper-body movements to match those measured on the user. The reason for this is that many VR application can be realized with only Headset and Hands tracking [18,24], which is known to cause nausea sensation if the tracked positions are of low accuracy, low frame rate or latency [28]. Lower-body motions of the avatar are reconstructed in accordance with the upper body.…”
Section: Introduction Virtual Humans (Vh)mentioning
confidence: 99%